1989
DOI: 10.1016/0921-4534(89)90306-7
|View full text |Cite
|
Sign up to set email alerts
|

Properties of La2CuO4 and related compounds

Abstract: We review the crystal chemical, electronic, magnetic and superconducting properties of La2CuO4 and related planar-cuprate materials, with emphasis on single-crystal results. Although magnetism due to divalent copper ions clearly is evident in nonsuperconducting crystals, experiments do not reveal any direct relationship between localized copper spins and high temperature superconductivity. We also indicate areas where important information is lacking for our understanding of these materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 102 publications
2
24
0
Order By: Relevance
“…The second entry is simply the first one rotated by 45° such that a direct comparison to the orthorhombic stoichiometric compound can be made. [47]. The Sr doped crystal was produced by Tanaka and Kojima using a travelling solvent/ floating zone system [48].…”
Section: Typical Resultsmentioning
confidence: 99%
“…The second entry is simply the first one rotated by 45° such that a direct comparison to the orthorhombic stoichiometric compound can be made. [47]. The Sr doped crystal was produced by Tanaka and Kojima using a travelling solvent/ floating zone system [48].…”
Section: Typical Resultsmentioning
confidence: 99%
“…62 Since in the LTO phase the critical field H c increases with decreasing T , at intermediate fields of ∼ 4 Tesla the spin-flip in La 2 CuO 4 at high temperatures has progressed to a higher degree than at low temperatures. 60 In contrast, at maximum field the DM moments in La 2 CuO 4 are ferromagnetically aligned down to 4 K (to the degree that is possible in a polycrystal 61 ). The susceptibility is smooth and increases monotonically with decreasing T and, moreover, is significantly larger than χ 2DHAF .…”
Section: Overview Of Sr and Eu Doping Dependencementioning
confidence: 99%
“…In contrast, in the LTT phase of the Eu-doped compound changes are rather weak. In the LTO phase, the influence of the field is particularly strong between 3 and 6 Tesla and follows from the first order spin-flip transition that can be induced for H c. 20,26,60,61 As is shown in Fig. 1 (a), at this transition the DM moments of adjacent CuO 2 planes, which are antiferromagnetically coupled in zero magnetic field, become ferromagnetically aligned.…”
Section: Overview Of Sr and Eu Doping Dependencementioning
confidence: 99%
“…A significant structural difference between La2CuO4 and the RE2CuO4 compounds is that Cu atoms are octahedrally coordinated by oxygens in La2CuO4, but in the RE2CuO4 materials, the coordination is square planar [ 4 ]. Electronically these two classes of CuO2-layer compounds also differ; Hall coefficient and thermoelectric power measurements on La2CuO4+6 suggest conduction by hole-like carriers, whereas, in RE2CuO4 the sign difference and magnitude of these effects imply a very small number of electron-like carriers [ 5 ]. Recently, Tokura et al [ 6 ] have found that substituting Ce into RE2_xCexCuO4, where RE = Pr, Nd and Sm, induces electron superconductivity with Tc ~ 20 K in these compounds which retain the I4/mmm structure of RE2CuO4 [ 7 ].…”
mentioning
confidence: 98%